FRISC score for selection of patients for an early invasive treatment strategy in unstable coronary artery disease. Issue 8 (14th July 2005) - Lagerqvist, B; Diderholm, E; Lindahl, B; Husted, S; Kontny, F; Ståhle, E; Swahn, E; Venge, P; Siegbahn, A; Wallentin, L
Abstract : Objective: To develop a scoring system for risk stratification and evaluation of the effect of an early invasive strategy for treatment of unstable coronary artery disease (CAD). Design: Retrospective analysis of a randomised study (FRISC II; fast revascularisation in instability in coronary disease). Setting: 58 Scandinavian hospitals. Patients: 2457 patients with unstable CAD from the FRISC II study. Main outcome measures: One year rates of mortality and death/myocardial infarction (MI). Methods: Patients were randomly assigned to an early invasive or a non-invasive strategy. From the non-invasive cohort independent variables of death or death/MI were identified. Results: Seven factors, age > 70 years, male sex, diabetes, previous MI, ST depression, and increased concentrations of troponins and markers of inflammation (interleukin 6 or C reactive protein), were associated with an independent increased risk for death or death/MI. In patients with ⩾ 5 of these factors the invasive strategy reduced mortality from 15.4% (20 of 130) to 5.2% (7 of 134) (risk ratio (RR) 0.34, 95% confidence interval (CI) 0.15 to 0.78, p = 0.006). Death/MI was also reduced in patients with 3–4 factors from 15.7% (80 of 511) to 10.8% (58 of 538) (RR 0.69, 95% CI 0.50 to 0.94, p = 0.02). Neither death nor death/MI was reduced in patients with 0–2 risk factors. Conclusion: In unstable CAD, this scoring system based on factors independently associated with an adverse outcome can be used shortly after admission to the hospital for risk stratification and for selection of patients to an early invasive treatment strategy.